Aplikasi Ujian Online Untuk SMA PKP JIS Dengan Metode Linear Congruential Generator (LCG) Berbasis Web - Heru Gunadi; Andrianingsih (STMIK Budi Darma, 2023)
Examinations are one way to evaluate the teaching and learning process in schools. Typically, school exams are still conducted conventionally using paper and writing materials, and grading is done directly by teachers. With the rapid development of information technology, some conventional systems have transitioned to computerized ones, including educational services such as online exams. Currently, the government mandates Computer-Based National Examinations (UNBK) for high schools (SMA/SMK/MA). Additionally, some national standard school exams known as USBN have adopted Computer-Based Test (CBT) systems. However, SMA PKP JIS still employs conventional methods for exams, which are considered less efficient given the current technological advancements. Manual processes for exam creation, duplication, evaluation, and answer sheet filling lead to various challenges, including high costs, lost answer sheets, and potential question leaks. Hence, this study aims to develop an online exam application using the Linear Congruential Generator (LCG) method based on a website. The LCG-based online exam application has been successfully created for SMA PKP JIS, providing a more efficient and paper-saving exam experience. Through testing using the blackbox testing method, this application has been proven to run well and according to its functionality. Its ability to facilitate the exam process efficiently makes it the right solution for PKP JIS High School. The score obtained from testing using the User Acceptance Testing (UAT) method is 329 or in the form of a percentage of 82.25% and is included in the